The massage connection : anatomy and physiology - Premkumar, Kalyani (Philadelphia, Pennsylvania : Wolters Kluwer Health/Lippincott Williams & Wilkin, 2012)
"Anatomy & Physiology: The Massage Connection . The main goal of this text has always been to create an anatomy and physiology text specifically for massage therapy students and practitioners and to write it at an appropriate level, focusing on the educational needs of the massage curriculum"--Provided by publisher.
1. An orientation to the human body -- 2. Integumentary system -- 3. Skeletal system -- 4. Muscular system -- 5. Nervous system -- 6. Endocrine system -- 7. Reproductive system -- 8. Cardiovascular system -- 9. Lymphatic system -- 10. Respiratory system -- 11. Digestive system -- 12. Urinary system
Includes bibliographical references and index
Keywords: Human anatomy; Human physiology; Massage